2016
DOI: 10.1016/j.ijheh.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Blood mercury levels and fish consumption in pregnancy: Risks and benefits for birth outcomes in a prospective observational birth cohort

Abstract: BackgroundTo avoid exposure to mercury, government advice on fish consumption during pregnancy includes information on fish species to avoid and to limit, while encouraging consumption of least two portions of fish per week. Some women may, however, chose to avoid fish completely during pregnancy despite potential benefits to the fetus.ObjectivesOur aims were to evaluate the effects of blood mercury levels in pregnant women on birth outcomes in the UK, and to compare outcomes in those who ate fish with those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 35 publications
3
40
0
2
Order By: Relevance
“…This finding supports a relationship between exposure to MeHg and birth weight [van Wijngaarden et al, 2014]. There were evidences for associations of B-Hg with increases in birth weight [Taylor et al, 2016]. LBW was more likely to happen among women who reside within 8 kilometers with fish consumption [Burch et al, 2014].…”
Section: Environmental Exposure Risk Factorsupporting
confidence: 76%
See 1 more Smart Citation
“…This finding supports a relationship between exposure to MeHg and birth weight [van Wijngaarden et al, 2014]. There were evidences for associations of B-Hg with increases in birth weight [Taylor et al, 2016]. LBW was more likely to happen among women who reside within 8 kilometers with fish consumption [Burch et al, 2014].…”
Section: Environmental Exposure Risk Factorsupporting
confidence: 76%
“…These factors also contribute to the role of maternal place of residence as a mediator of maternal stress and adverse reproductive outcomes among women [Miranda et al, 2009]. One study found evidence of the associations between B-Hg with birth weight increases [Taylor et al, 2016]. Mothers who lived in the highlands were at risk for hypoxic fetus that caused neonatal asphyxia.…”
Section: Environmental Exposure Risk Factormentioning
confidence: 99%
“…The role of Hg as a toxicant in sexual reproduction and pregnancy is quite neglected compared with the great attention spent on reports regarding neurotoxicology from this heavy metal. Despite some contradictory evidence, the role of Hg in human reproduction is going to be a major alarming issue . This MiniReview is aimed at analysing the published documentation about the effects of organic and inorganic Hg in human fertility, the outcome of childbirth, congenital abnormalities, loss of pregnancy and menstrual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Taylor and colleagues conducted in the UK found weak evidence of a protective effect of blood mercury levels measured in the mother early in pregnancy (median 11 weeks) and PTB, but this association attenuated in adjusted models (100). In a study population of women who were predominantly African American or of Caribbean decent, investigators found a protective effect of higher mercury levels in maternal urine during the last trimester of pregnancy, but the estimate was imprecise (101).…”
Section: Environmental Chemicals and Ptbmentioning
confidence: 99%